La huelga y el cierre empresarial / Manuel Alonso García ; [colaboradores] Fernando Almendros Morcillo ... [et al.] - Almendros, Fernando; Alonso García, Manuel (1926-1988) (Estudios)
Bibliografía: p. 245-246